Dynamic tensile mechanical behavior of polyurethane films incorporated with functionalized graphene oxide. (19th April 2022) - Wang, Xiangyang; Tang, Xiu-Zhi; Hu, Xiaoping; Wang, Pengfei
Abstract: Since high-speed collisions often give rise to catastrophic damage, investigating the enhancement and dynamic behavior of composites is essential. Herein, graphene oxide (GO) and its surface-modified derivative were separately incorporated into the polyurethane matrix and their dynamic mechanical properties were examined and compared. A drop-weight dynamic tension device was used to characterize the mechanical properties of composites. The collected results show significant improvement in failure strength while incorporating GO as the nanofiller. And, the slightly reduced graphene oxide (SRGO) grafted with polyethyleneimine (SRGO-PEI) is beneficial in improving the plastic stress. The high-speed deformation process reveals severe strain localization before the break. The morphology of fracture surfaces indicates the SRGO-PEI plays a vital role in hindering crack propagation. Then the constitutive equation was derived to describe the stress-strain curves of modified polyurethane films. This work involves the synergistic effect between surface modification of nanofillers and the dynamic behavior of polymer-based composites, which could be regarded as a guideline for designing the composites under high-velocity impact environments. Graphical abstract: Image 1 Highlights: Dynamic behavior of graphene oxide and its surface modified derivative polyurethane were investigated. Constitutive equation was derived to describe the stress-strain curves of modified polyurethane film. SRGO-PEI modified surface plays a vital role in hindering crack propagation.